DESAIN INTEGRASI NILAI-NILAI SOSIAL MENURUT AGAMA ISLAM KE DALAM POKOK BAHASAN HUBUNGAN SOSIAL PADA MATA PELAJARAN IPS KELAS VIII SMP NEGERI 2 ANJIR PASAR - Sarkani Sarkani (Universitas Lambung Mangkurat, 2012)
Government efforts to improve the quality of education, especially in the areas of curriculum integration to maintain a general knowledge (in this case subjects IPS) with the values and religious norms (social values) has been developed in the Competency-Based curriculum (CBC) and Unit Level Education curriculum (SBC). This is a realization of the national education goals. Based on observations in SMP Negeri 2 Anjir Pasar District Market District Anjir Barito Kuala, that the integration of social values according to the religion of Islam into the subject of social relationships in social studies subjects have not been developed and implemented. Due to the lack of an integrated instructional design and the lack of teachers' ability to innovate in learning. The research objective to determine the design intergasi social values according to the religion of Islam into the subject of social relationships on the subjects social studies class VIII. The study uses a qualitative approach, namely the approach of trying to obtain descriptive data, speech or writing, and behavior can be observed.Research using qualitative methods with the steps of the research design Suheri adopting measures Bruog research and Gall.The results of this study found a design model of integration in social studies learning. Than 2 times the design implementation of integration in social studies learning, it is known that the first meeting of the obtained value of 5.80 with 51.44% completeness, while the obtained value of 6.14 second meeting with the thoroughness 71.42%. Kata Kunci : Desain Integrasi, Pembelajaran Terpadu, Hubungan Sosial, Nilai Sosial